Engaging the doctrine of the Holy Spirit : love and gift in the Trinity and the church - Levering, Matthew, 1971- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2016)
Distinguished theologian Matthew Levering offers a historical examination of the doctrine of the Holy Spirit, defending an Augustinian model against various contemporary theological views. A companion piece to Levering's Engaging the Doctrine of Revelation, this work critically engages contemporary and classical doctrines of the Holy Spirit in dialogue with Orthodox and Reformed interlocutors. Levering makes a strong dogmatic case for conceiving of the Holy Spirit as love between Father and Son, given to the people of God as a gift.
The Holy Spirit as love and gift -- Naming the Holy Spirit: east and west -- The Holy Spirit and the filioque -- The Holy Spirit and Jesus Christ -- The Holy Spirit and the church -- The Holy Spirit and the unity of the church -- The Holy Spirit and the holiness of the church.
Includes bibliographical references (pages 373-422) and index.
Keywords: Holy Spirit -- History of doctrines; Holy Spirit -- History of doctrines